Ideologies in outdoor public signs in Bali: A critical pragmatic and linguistic landscape study - Widiatmika, Putu Wahyu; Sosiowati, I Gusti Ayu Gde (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2024)
Outdoor public signs found in Bali contain ideologies and messages that can be mistakenly understood, potentially triggering conflicts. This study aims to identify and analyze the underlying ideology and the language functions in outdoor public signs found in Bali from the perspective of critical pragmatics and linguistic landscape. The data of this study were outdoor public signs that contain power relation from government and private stakeholders. The data were collected through observation and photography. The data were analyzed through referential and pragmatic identity methods with descriptive-qualitative approach. The theories applied were Halliday's context of situation, Yule's speech act, Fairclough's critical discourse analysis, and Saussure's signifier and signified. The results show that outdoor public signs in Bali have underlying ideologies, such as ethnocentrism, xenocentrism, and ecologism. The language functions are directive, commisive, and expressive. The ideologies represented by the language used can potentially cause conflicts as they may be sensitive to certain ethnic groups. The findings highlight the significance of critically examining public signage to understand its influence in shaping social dynamics and potential for unintended consequences.